PENGARUH STRUKTUR AUDIT, PEMAHAMAN GOOD GOVERNANCE DAN PENERAPAN TEKNOLOGI INFORMASI TERHADAP KINERJA AUDITOR (Studi Empiris Pada Kantor Akuntan Publik Di Jakarta Pusat) - Wiwik Pratiwi; Nia Aziza Misqih (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2018)
This study aims to determine the effect of audit structure, understanding of good governance and application of information technology to auditor performance. The population in this study is all auditors working in Public Accounting Firm (KAP) located in Central Jakarta. The sampling technique used is nonprobability sampling technique. The author conducted a sample at 24 Public Accounting Firm registered in Central Jakarta. Data analysis technique begins with descriptive statistical test, followed by data quality test consisting of validity and reliability test, normality data test, classical assumption test consist of regression normality test, multicollinearity test, heterokedastisity test, regression linearity test. Hypothesis test using t test, f test and coefficient of determination.  The results of this study indicate that the audit structure, the understanding of good governance and the application of information technology has a significant influence on the performance of auditors. Audit structure, understanding of good governance and application of information technology together have a significant influence on auditor performance. Keywords: Auditor performance, audit structure, good governance and application of            information technology.